Composition of ex vivo perfusion solutions and kinetics define differential cytokine/chemokine secretion in a porcine cardiac arrest model of lung preservation - Radomsky, Lena; Koch, Achim; Olbertz, Carolin; Liu, Yongjie; Beushausen, Kerstin; Keil, Jana; Rauen, Ursula; Falk, Christine S.; Kühne, Jenny F.; Kamler, Markus (Frontiers in Cardiovascular Medicine, 2023)
Background Ex vivo lung perfusion (EVLP) uses continuous normothermic perfusion to reduce ischemic damage and to improve post-transplant outcomes, specifically for marginal donor lungs after the donation after circulatory death. Despite major efforts, the optimal perfusion protocol and the composition of the perfusate in clinical lung transplantation have not been identified. Our study aims to compare the concentration levels of cytokine/chemokine in different perfusion solutions during EVLP, after 1 and 9 h of cold static preservation (CSP) in a porcine cardiac arrest model, and to correlate inflammatory parameters to oxygenation capacities. Methods Following cardiac arrest, the lungs were harvested and were categorized into two groups: immediate (I-EVLP) and delayed EVLP (D-EVLP), after 1 and 9 h of CSP, respectively. The D-EVLP lungs were perfused with either Steen or modified Custodiol-N solution containing only dextran (CD) or dextran and albumin (CDA). The cytokine/chemokine levels were analyzed at baseline (0 h) and after 1 and 4 h of EVLP using Luminex-based multiplex assays. Results Within 4 h of EVLP, the concentration levels of TNF-α, IL-6, CXCL8, IFN-γ, IL-1α, and IL-1β increased significantly (P < 0.05) in all experimental groups. The CD solution contained lower concentration levels of TNF-α, IL-6, CXCL8, IFN-γ, IL-2, IL-12, IL-10, IL-4, IL-1RA, and IL-18 (P < 0.05) compared with those of the Steen solution. The concentration levels of all experimental groups have correlated negatively with the oxygenation capacity values (P < 0.05). Protein concentration levels did not reach statistical significance for I-EVLP vs. D-EVLP and CD vs. CDA solutions. Conclusion In a porcine cardiac arrest model, a longer period of CSP prior to EVLP did not result in an enhanced protein secretion into perfusates. The CD solution reduced the cytokine/chemokine secretion most probably by iron chelators and/or by the protecting effects of dextran. Supplementing with albumin did not further reduce the cytokine/chemokine secretion into perfusates. These findings may help in optimizing the preservation procedure of the lungs, thereby increasing the donor pool of organs.